An Applied Learning Experience Field Research and Reporting at the 2012 National Party Conventions - Carlson, Carolyn S.; Azriel, Joshua; DeWitt, Jeff; Swint, Kerwin (International journal for the scholarship of teaching and learning, 2014)
Scholarship in teaching and learning demonstrates how academic understanding may be best achieved, and values of civic engagement best inculcated, when class materials are delivered within a experiential context. The goal for instructors, therefore, is to develop pedagogic techniques and teaching platforms that enhance learning by doing by directly engaging students with educational content. Courses that focus on American political processes provide especially fruitful opportunities for such applied learning experiences. In this paper, we discuss and assess experiential learning as facilitated in a pair of undergraduate courses taught at a southern state university that focused on the study of American politics at national party conventions. As a primary requirement in "Political Party Conventions Field Study" and "Reporting at the Party Conventions," political science and communication students, and four supervising faculty, traveled to the 2012 Democratic National Convention and Republican National Convention where they produced political research using field observation and survey methodologies and professional-style news reporting. Survey data collected before and after the convention indicate that students engaged in such experiential learning projects develop a more substantive understanding of the subject matter under study, enhanced motivation for learning, and greater feelings of academic achievement and citizenship.